Prawo do pracy w międzynarodowych systemach ochrony praw człowieka - Jarczyński, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Unemployment related to the Great Depression was one of the factors which brought the Nazi Party to power in Germany and, consequently, one of the causes of World War II and the crisis of human rights protection. After this experience, the international community worked to establish a universal law system to protect human rights, including the right to work. This article is an overview of the most significant legal acts of international law regarding the right to work existing in the global, specialized, and regional human rights protection systems. This paper presents regulations related to the right to work, the right to annual leave, shift patterns, participation in unions, and protection from discrimination.
Keywords: international law; human rights; right to work